PENERAPAN MODEL ILUMINATIF DALAM EVALUASI PEMBELAJARAN IPS DI SD NEGERI GEBANGAN, PENGASIH, KULON PROGO - Rina Ambarwati; Esti Setiawati (Jurnal Sosialita, 2026)
This study aims to describe the application of the illuminative model in the evaluation of Social Studies (IPS) learning at Gebangan Elementary School, Pengasih, Kulon Progo. The illuminative model is used as an alternative approach to evaluate learning as a whole, not only focusing on academic results, but also examining the process, interactions, and contextual factors that influence learning success. This study employs a descriptive qualitative approach with an illuminative evaluation model in social studies learning. Data collection techniques consist of observation, in-depth interviews, and documentation. The data analysis was carried out using an interactive model, which includes the steps of data reduction, data display, and conclusion drawing. The results of the study indicate that the application of the illuminative model provides a deeper understanding of the IPS learning process in schools. Several advantages were found, such as exploring student and teacher perceptions and identifying obstacles that were not detected through conventional evaluations. However, there are also challenges such as limited innovation in learning methods, minimal active student participation, and the focus of evaluation which is still dominant on the cognitive aspect. The application of the illuminative model has a positive impact on increasing teacher awareness to innovate and encourage more active student involvement. This study recommends that the illuminative model be applied sustainably to improve the quality of IPS learning, through teacher training, development of learning media, and involvement of parents and the community in the education process.